4D Printing of Freestanding Liquid Crystal Elastomers via Hybrid Additive Manufacturing (Adv. Mater. 39/2022). Issue 39 (27th September 2022) - Peng, Xirui; Wu, Shuai; Sun, Xiaohao; Yue, Liang; Montgomery, S. Macrae; Demoly, Frédéric; Zhou, Kun; Zhao, Ruike Renee; Qi, H. Jerry
Abstract : 4D Printing In article number 2204890, Ruike Renee Zhao, H. Jerry Qi, and co‐workers report a hybrid 4D printing method to fabricate freestanding liquid crystal elastomers "on‐the‐fly" by using laser‐assisted direct ink writing. This process is integrated with Digital Light Processing for printing optional structural or sacrificial materials to create active architectures, such as active tensegrities, loading‐bearing actuators, and 3D liquid crystal lattices, in a one‐step additive process.